December Love - Hichens, Robert, 1864-1950 (Salt Lake City, UT : Project Gutenberg, 2006)
"December Love" by Robert Hichens is a novel likely written in the early 20th century. The narrative primarily revolves around Alick Craven, a member of the Foreign Office, and his interactions with his friend Francis Braybrooke, who introduces him to the intriguing figure of Lady Adela Sellingworth, a once-famous beauty of London society who has retreated from the social scene. The story delves into themes of aging, beauty, and the pursuit of love and admiration as reflected through Lady Sellingworth's life choices and her enigmatic past. The opening of "December Love" introduces readers to Alick Craven and his casual conversation with Francis Braybrooke at a club in London. Braybrooke is fascinated with societal dynamics and brings up Lady Sellingworth, eliciting Craven's curiosity about her seemingly abrupt withdrawal from society after a notable career. Craven learns of her lost jewels and the mystery surrounding her indifference to the theft, leading to a growing intrigue towards meeting this once-reigning beauty. The stage is set for a deeper exploration of Lady Sellingworth's complex character as Craven is invited to tea with her, hinting at the emotional undercurrents and societal commentary that will unfold throughout the novel. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/December_Love
Release date is 2006-04-22
Produced by Dagny; John Bickers; David Widger
Keywords: Love stories; Jewelry theft -- Fiction; Mystery fiction; London (England) -- Social life and customs -- 20th century -- Fiction